Issue networks on the Web: a proposal of components and characterization - Miguel Castillejo Sierra; Lluís Codina; Carles Pont (Hipertext.net, 2014)
Many types of research on Social Sciences, Political Sciences and Market Sciences present the need to obtain information about the opinion or public reaction to certain topics. The Web is a source of information which might help satisfying this need, but to achieve this goal it is necessary to develop concepts and methodologies allowing to understand how it works, and to extract the different forms of knowledge it contains. This article presents the concept of “issue network”, and through a theoretical revision of hyperlink studies, the concepts of “issue” and “actor” and the concept of issue network itself, we expose its characteristics, the problems it solves and the possibilities it offers to opinion studies.